Psychological contract and turnover intention among healthcare assistants in a hospital environment: a multi-center cross-sectional analysis - Yang, Jing-ping; Xue, Feng; Zhang, Lin; Zhang, Qiaoxian (Frontiers in Psychology, 2025)
AimThe aim of this study was to examine the correlation between psychological contract and turnover intention among hospital healthcare assistants.DesignA multi-center cross-sectional analysis was employed in this study.MethodsA survey was conducted among healthcare assistants employed at 10 Grade A tertiary hospitals in Fuzhou using a psychological contract scale, turnover intention scale, and demographic questionnaire.ResultsA total of 540 healthcare assistants participated in the study. The turnover intention scores varied from 6 to 22, with an average score of 11.51 ± 3.54. The number of individuals with a very low turnover intention amounts to 40 (7.40%), those with a low turnover intention total 302 (55.93%), individuals with moderate turnover intention numbered 195 (36.11%), and those with a high turnover intention are 3 (0.56%).The psychological contract scores among healthcare assistants ranged from 42 to 195, with an average score of 153.90 ± 33.18. A hierarchical multiple regression analysis was performed and psychological contract increased the explanatory power of the turnover intention regression model by 38.4%.ConclusionMaintaining a high level of psychological contract is beneficial for reducing the turnover intention of healthcare assistants. Hospital managers can adopt certain measures from the perspective of psychological contract to stabilize the team of healthcare assistants.